Pendampingan Pembuatan Modul Ajar Berbasis Digital bagi Guru SMP di Kota Batam Menggunakan Pendekatan Project Based Learning dengan Framework CDIO - Himawan Mochtoha; Maryani Septiana; Rahmat Hidayat; Nur Rahmah Andayani; Muslim Ansori; Atiqotun Nisa; Slamet Soebagiyo; Sri Zuliarni; Riza Khusniah (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2026)
The rapid advancement of information and communication technology has fundamentally transformed the educational landscape, yet a significant gap persists between teachers' digital competency and the technological demands of modern classrooms. This community service program aimed to assist junior high school teachers in Batam City in developing digital-based teaching modules through a project-based learning (PBL) approach using the Conceive-Design-Implement-Operate (CDIO) framework. Conducted from April to November 2025, the program involved 20 teachers from five public junior high schools (SMPN 6, SMPN 38, SMPN 53, SMPN 59, and SMPN 63 Batam), supported by students from the D4 Applied Business Administration Program at Politeknik Negeri Batam. A preliminary survey revealed that 67% of teachers still used conventional teaching methods, 78% lacked digital development skills, and 92% required technical assistance. The program produced a comprehensive range of digital teaching materials, including interactive e-modules (PDF), educational videos (MP4), interactive games using Quizizz, Kahoot!, Pictoblox, and Scratch, interactive presentations designed with Canva, and Augmented Reality (AR)-based learning media using Assembler Edu. These materials were developed for subjects including Civics Education, Informatics, Natural Sciences, and Riau Islands Cultural Studies. The results demonstrate that structured mentoring through the CDIO framework effectively enhanced teachers' digital competency and produced high-quality, curriculum-aligned digital teaching materials. This initiative contributed to broader educational quality improvement and serves as a replicable model for similar community service programs across the region.